Phycoremediation potential with ultrastructural and biochemical response of Kirchneriella lunaris to metribuzin - Yılmaz Öztürk, B.; Dağlıoğlu, Y.; Tezcan Ün, Ü.; Dağ, İ. (International journal of environmental science and technology (Tehran), 2025)
Metribuzin (MET) is a triazine herbicide used for the protection of weeds in agriculture, and its frequent and inexpensive use poses a significant danger to untargeted algae and natural water systems. There is still much information available regarding the study of the growth effects of herbicides on photosynthetic organisms, especially microalgae, the diversity of their specific potentiation, distant light, and damage to biological targets. Additionally, it is not fully understood how organisms adapt to these chemicals. In this study, the cellular response of Kirchneriella lunaris microalgae to MET was investigated for the first time, to our knowledge, by exposure to sublethal concentrations (0, 25, 50, and 100 μg/mL) for 72 h. Our data showed the effects of MET uptake on growth, photosynthetic ability, and toxicity in K. lunaris cells. MET increased the organism’s photosynthetic activity, MDA (Malondialdehyde), H 2 O 2 (Hydrogen peroxide), and ROS production depending on dose and time. It also induced oxidative stress and activated enzymatic and non-enzymatic defense mechanisms. While the levels of non-enzymatic antioxidant systems such as DPPH radical scavenging activity and proline content increased depending on MET concentration, protein content decreased. Ultrastructural findings obtained by transmission electron microscope (TEM) support that MET has multitarget effects on K. lunaris , especially when applied at a concentration of 50 µg/mL. Our findings show that the microalgae used can acclimate to MET as the concentration increases. Growth rate, oxidative stress markers, enzymatic activities, and TEM analyses are useful parameters in ecotoxicological evaluation, but detailed studies on the subject are needed. Graphical abstract